Global Attractivity for Three Species Lotka-Volterra Systems with Delays. Issue 3 (October 2020) - Halik, Azhar; Omar, Ahmatjan
Abstract: This paper studies a type of non-autonomous three-species Lotka-Volterra(L-V) predator-prey-competitive systems with time delays is discussed. Several sufficient conditions on the global attractivity of the system are derived by employing the Lyapunov function method.